Peran Mahasiswa sebagai Agen Perubahan dalam Pelestarian Lingkungan Hidup: Studi Kasus : Organisasi Mapasta UINSU & Mahasiswa FEBI UINSU - Sry Rahayu Ningsih Sitorus; Pajhar Ainun Berutu; Arini Handayani; Muhammad Ariansyah; Sari Wulandari (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the strategic role of students as agents of change in environmental conservation, with a focus on the activities of the Nature Lovers Student Organization (MAPASTA) at UINSU and students at FEBI UINSU. Using a descriptive qualitative approach, data was collected through in-depth interviews with five informants. The findings reveal that students play a crucial role in educating the public, initiating concrete environmental actions, and advocating for sustainability issues through social media and campus activities. Despite challenges such as low collective awareness, students remain capable of serving as catalysts for change through creative and collaborative approaches. These findings emphasize the importance of institutional support and capacity building for students to achieve sustainable environmental sustainability.